Ratifikasi WTO dan Dampaknya pada Pembangunan dan Pembaharuan Hukum Ekonomi Indonesia (Suatu Tinjauan Ontologis) - Zulfikar Ali Butho (Universitas Bandar Lampung (UBL), 2011)
This study is about WTO ratification and its impa on economic development andIndonesia legal reform (an ontological approach). WTO law is based on positivismneoliberalismparadigm. WTO law substance againsts pancasila paradigm and 33articles of the 1945 constitution. In addition to the substance of WTO law negatesthe substance of the article 7 of legal drafting regulation, it will have an impact on:(a) loss of Pancasila as the position fundamentalnorm paradigm and must make thelegal establishment of the indonesian economy as fundamental WTO law, (b) loss ofPancasila as the position recht and must make the legal establishment of theindonesian economy as recht WTO law paradigm, (c) loss of standing of Pancasilaparadigm as the validity of the presupposition and the needs for the establishment ofthe economic laws in indonesia to the WTO as a presupposition the validity of the act